Magnetic Resonance Imaging of Thoracic Aortic Dissections - Sax, Steven L. (1990)
Magnetic resonance imaging is an excellent noninvasive method for evaluating thoracic aortic dissections. A variety of magnetic resonance scans of aortic dissections are shown, documenting the ability of magnetic resonance to image the true lumen, the false channel, and the intimal septum. Detail is provided on magnetic resonance imaging techniques and findings. (Texas Heart Institute Journal 1990;17:262-70)